A Study on Awareness About Harmful Effects of Tobacco Use Among Rural Population in Dehradun District of Uttarakhand - Imtiaz, Danish; Kandpal, Sunit Dutt; Juyal, Ruchi; Shrotriya, Ved Prakash (National Journal of Community Medicine, 2015)
Background: Tobacco use is one of the leading preventable causes of premature death, disease and disability around the world. Ob- jective of this study was to assess the awareness of current tobac- co users towards harmful effects of tobacco in the rural popula- tion. Method: In the rural area households were selected by systematic random sampling and all the current tobacco users in the selected house were personally interviewed about the harmful effects of tobacco by using a pre-structured and pretested schedule. Results: Overall interviewed 993 current tobacco users (Males- 84.3%, Female-15.7%), most (87.4%) were aware of the hazardous effects of tobacco. Most knew that tobacco consumption can lead to lung cancer and oral consumption of tobacco can lead to oral cancer. Television (46.2%) was the main source of this infor- mation. Males (87.7%) were found to be more aware as compared to females (62.2%) regarding the warning labels on tobacco pack- ets. Conclusion: Although current tobacco users were found to be aware regarding harmful effects of tobacco but still there is a need for initiating community awareness programmes targeting the rural population and making them aware of the various health consequences of tobacco use.